Comprehensive Analysis of the Expression and Prognosis for MMPs in Human Colorectal Cancer - Yu, Jing; He, Zhen; He, Xiaowen; Luo, Zhanhao; Lian, Lei; Wu, Baixing; Lan, Ping; Chen, Haitao (Frontiers in Oncology, 2021)
Abstract Background: Previous study implicated that genes of matrix metalloproteinases (MMPs) family play an important role in tumor invasion, neoangiogenesis, and metastasis. However, the diverse expression patterns and prognostic values of 24 MMPs in colorectal cancer yet to be analyzed. Methods: In this study, by integrating public database and our data, we first investigated the expression levels and protein levels of MMPs in patients with colorectal cancer. Then by using TCGA and GEO dataset, we evaluated the association of MMPs with clinicopathological parameters and prognosis of colorectal cancer. Finally, by using the cBioPortal online tool, we analyzed the alterations of MMPs and did the network and pathway analyses for MMPs and their nearby genes. Results: We found that, MMP1, MMP3, MMP7, MMP9-MMP12 and MMP14 were consistently up-regulated in public dataset and our samples. While MMP28 was consistently down-regulated in public dataset and our samples. In the clinicopathological analyses, up-regulated MMP11, MMP14, MMP16, MMP17, MMP19 and MMP23B were significantly associated with a higher tumor stage. In the survival analyses, up-regulated MMP11, MMP14, MMP17 and MMP19 were significantly associated with a shorter progression-free survival (PFS) time and a shorter relapse-free (RFS) time. Discussion: This study implied that MMP11, MMP14, MMP17 and MMP19 are potential targets of precision therapy for patients with colorectal cancer.